Participamos en un debate sobre el uso de pirotécnicos en la navidad y año nuevo - Arroyo Flores, Marixa (2018)
The debate is a teaching-learning strategy that consists in the confrontation of different points of view in order to arrive at a soundly supported judgment. Cattani defines the debate as "a competition (a challenge, a challenge) in which, unlike what happens in a simple discussion, there is a third party (a judge, an audience) whose approval is sought by the two contenders." (Cattani, 2003) The pyrotechnics have become part of the Christmas traditions and used for various celebrations. They are very noisy, colorful and beautiful, however, used inappropriately, they are quite dangerous. The pyrotechnic can provide moments of healthy entertainment for the whole family and should be used by adults with care and safety, never by children, as they represent a high risk and danger. All fireworks, without exception, are dangerous and their management requires experience and great care.